PRINSIP DAKWAH LEMBAGA PENDIDIKAN ALKHAIRAAT DI KOTA TERNATE - Samlan Ahmad (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
Lately, there are many problems of religious behavior which partially understand religion, causing many deviations in the name of religion and belief. Roughness and hatred towards other groups in the name of religious teachings and "heretical" religious understanding, is the impact of human acceptance of religious teachings that are not accompanied by good education and understanding of religious knowledge, so that preaching through educational institutions becomes the choice to build an understanding of Islam that is comprehensive and inclusive. The results of this study indicate that (1) The concept of Alkhairaat preaching follows the Habib Idrus style of preaching namely subtle and sympathetic, with the style of movement of a number of scholars who introduce movements in various regions including the archipelago, using the concept of tabsyit lil ummah which makes the messages of religious teachings as news or good news for the Ummah. (2) The form of da'wah conducted by Alkhairaat is by developing educational institutions that are oriented to the formation of knowledge, attitudes and behavior of the community in accordance with the guidance of the teachings of Islam